PROSES COLLABORATIVE GOVERNANCE DALAM PENGEMBANGAN OBJEK WISATA TELAGA JONGE PACAREJO KECAMATAN SEMANU KABUPATEN GUNUNGKIDUL - Suci Kurniati, Verena; Larasati Setianingsih, Endang (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2025)
The development of Telaga Jonge tourist attraction in Pacarejo, Semanu District, Gunungkidul Regency involves Jonge Raya Tourism Awareness Group (Pokdarwis), Pacarejo Village Government, Gunungkidul Tourism Office, local communities, and local businesses. This research is motivated by the great potential of Telaga Jonge tourism but has not been optimally developed, as well as the existence of conflicts related to management. This research uses Ansell and Gash's collaborative governance theory with the research objective to analyze the collaborative governance process in Telaga Jonge and identify the factors that drive and hinder the process. The research method used is descriptive qualitative with data collection techniques through interviews, observations, and documentation. The results of the study show that the collaborative governance process in Telaga Jonge is still in its early stages and has not yet run effectively. The main challenge lies in building trust and mutual understanding among the actors involved. Weak institutional design, lack of transparency, and differences in perceptions of tourism potential ownership are the main inhibiting factors